ANALYSIS OF THE ECONOMIC SITUATION IN WESTERN EUROPE - L. M. Rubaeva; A. A. Datieva (Вестник университета, 2021)
The article considers the issue of achieving the most stable socio-economic situation in the countries of Western Europe. The paper highlights socio-economic factors that characterize states with a developed economic system. The authors make a comparative analysis of the macroeconomic indicators of countries with a developed socio-economic situation: Germany, France and the United Kingdom. The study notes the relationship between the sectors of the economy that have allowed developed countries to achieve the greatest results at present time. Based on the study, the authors identify the main provisions that stimulate the economic and social development of the considered states.